Quantitative characterization of the regulation of iron metabolism in glioblastoma stem‐like cells using magnetophoresis. Issue 7 (24th April 2019) - Park, Kyoung‐Joo J.; Kim, James; Testoff, Thomas; Adams, Joseph; Poklar, Miranda; Zborowski, Maciej; Venere, Monica; Chalmers, Jeffrey J.
Abstract: This study focuses on different iron regulation mechanisms of glioblastoma (GBM) cancer stem‐like cells (CSCs) and non‐stem tumor cells (NSTCs) using multiple approaches: cell viability, density, and magnetophoresis. GBM CSCs and NSTCs were exposed to elevated iron concentration, and their magnetic susceptibility was measured using single cell magnetophoresis (SCM), which tracks the magnetic and settling velocities of thousands of individual cells passing through the magnetic field with a constant energy gradient. Our results consistently demonstrate that GBM NSTCs have higher magnetic susceptibility distribution at increased iron concentration compared with CSCs, and we speculate that it is because CSCs have the ability to store a high amount of iron in ferritin, whereas the free iron ions inside the NSTCs lead to higher magnetic susceptibility and reduced cell viability and growth. Further, their difference in magnetic susceptibility has led us to pursue a separate experiment using a quadrupole magnetic separator (QMS), a novel microfluidic device that uses a concentric channel and permanent magnets in a special configuration to separate samples based on their magnetic susceptibilities. GBM CSCs and NSTCs were exposed to elevated iron concentration, stained with two different trackers, mixed and introduced into QMS; subsequently, the separated fractions were analyzed by fluorescent microscopy. The separation results portray a successful label‐less magnetic separation of the two populations. Abstract : This study explores the iron regulation mechanism of the glioblastoma (GBM) cancer stem cells (CSCs) and non‐stem tumor cells (NSTCs), yielding various questions regarding the iron‐storage methods of these cancer cells as well as feasibility to magnetically separate unlabeled, iron‐rich GBM CSCs and NSTCs using a novel magnetic separation system, a quadrupole magnetic sorter.